Variação Sazonal do Ciclo Médio Diário dos Fluxos de Co2 em uma Floresta de Araucária - Oliveira, Pablo E. S.; Acevedo, Otávio; Moraes, Osvaldo L. L.; Zimermann, Hans R.; Teichrieb, Claudio A.; Santos, Daniel M. (Ciência e Natura, 2011)
.